A kinematic analysis of the upper limb during the topspin double-handed backhand stroke in tennis. Issue 9 (21st October 2022) - Busuttil, Nicholas A.; Reid, Machar; Connolly, Molly; Dascombe, Ben J.; Middleton, Kane J.
ABSTRACT: The purpose of this study was to compare double-handed backhand kinematics of the non-dominant wrist of tennis players using either an eastern or continental grip position with the non-dominant hand. Trajectory data were captured using sixty reflective markers on sixteen sub-elite right-handed tennis players using a 12-camera VICON motion capture system (250 Hz). Participants executed double-handed backhands using two non-dominant grip positions (Eastern [E] and Continental [C]), aiming for two crosscourt zones (Deep [D] and Short [S]), totalling to four conditions (ED, CD, ES and CS). Three successful attempts from each condition were selected for analysis. The eastern grip demonstrated faster horizontal racket head velocity compared to the continental grip. However, no differences were observed in accuracy or spin rate between grips ( p > 0.05). In the non-dominant upper limb, elbow flexion was smaller in the continental condition throughout the swing, whilst wrist extension and ulnar deviation was larger. Collectively, these data suggest that the continental grip may place the wrist in a position vulnerable to overuse injury. Future research into the kinetics of the double-handed backhand would help better understand the onset of ulnar-side wrist pain in tennis.